2019
DOI: 10.1007/s13197-019-03720-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydration techniques on bioactive compounds in hawthorn slices and their correlations with antioxidant properties

Abstract: Hawthorn fruits are rich in nutrients and antioxidant compounds. Dehydration is the major processing and preservation method for hawthorn fruits. The rates of moisture loss; polyphenol, flavonoid and triterpenoid acid contents; and antioxidant activities and their relationships were investigated in hawthorn slices that were dried by four dehydration techniques (microwave drying, solar drying, hot air drying and freeze drying) under different operation conditions. The results showed that both the drying method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
3
25
0
1
Order By: Relevance
“…In this method, the cell structure is mostly damaged, which is due to the long exposure of the product to the heat. In other studies, such as on Pistacia atlantica [ 47 ], cabbage [ 27 ], and hawthorn fruit [ 3 ], the hot-air method had the lowest amount of phenolic content compared to other drying methods, which is similar to the results of this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In this method, the cell structure is mostly damaged, which is due to the long exposure of the product to the heat. In other studies, such as on Pistacia atlantica [ 47 ], cabbage [ 27 ], and hawthorn fruit [ 3 ], the hot-air method had the lowest amount of phenolic content compared to other drying methods, which is similar to the results of this study.…”
Section: Resultssupporting
confidence: 90%
“…Freeze-drying had the highest AC, which was due to the lack of thermal degradation of heat-sensitive compounds. Liu et al [ 3 ] conducted drying of hawthorn fruit in different drying methods (i.e., hot air, microwave, solar, and freeze) and showed that the highest amount of AC was obtained using freeze-drying. Turkmen et al [ 55 ], Izli et al [ 7 ], Kaveh et al [ 56 ], and Szychowski et al [ 5 ] investigated the AC when drying cherry laurel, kiwifruit, green pea, and quince using different drying methods, respectively, and found that the AC in the freeze-dried samples was higher than other drying methods, which was consistent with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, Crataegus berries and flowers are officially recognized as herbal raw materials and have been included in European, American, and Canadian pharmacopeias. Recent research confirmed and extended the possibilities of the traditional use of this plant, among others, to anti-inflammatory [ 8 , 9 ], anti-oxidant [ 10 , 11 ], anti-aging [ 12 ], anti-depressant [ 13 ], anti-viral, anti-fungal, anti-bacterial [ 14 ], hypoglycemic, hepatoprotective [ 15 ], gastroprotective [ 16 ], immunostimulatory, hypolipidemic, hypocholesterolemic, and anti-atherosclerotic effects [ 17 ]. Furthermore, Crataegus extracts are considered as putative therapeutic agents for the treatment of hepatocellular carcinoma, breast cancer, melanoma, and colorectal cancer [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 97%
“…As indicated above, many beneficial properties have been attributed to hawthorn, including anticancer [55], anti-HIV, anti-diabetic [56], and anticoagulant activity [57], cardioprotective effects [58][59][60][61][62][63][64][65], hepatoprotective effects, antihyperglycemic and antihyperlipidemic activities, wound healing effects [66], antimicrobial effects, gastroprotective effects, treatment of metabolic syndrome [67], regulation of cholesterol homeostasis [68], anti-atherosclerosis effects [69][70][71][72], anti-aging effects [73], ischemia protective effects [74], treatment of cognitive disorders, neuroprotective effects, regulating gastrointestinal motility [75], anti-inflammatory activities [76,77], regulation of the gut-brain axis [78], treatment of hypertension [79], antioxidant activity [80][81][82][83][84][85], anti-hypoxic activities [86], antidepressant effects [87], anti-Alzheimer's effects, and treatment of intestinal microbial disorder [88].…”
Section: In Vitro and In Vivo Therapeutic Potentials Of Hawthorn: An mentioning
confidence: 99%